Subjectivity and intersubjectivity in psychiatric diagnosis - Fuchs, Thomas (Psychopathology, 2010)
The establishment of criteriological diagnostic systems since the 1980s has increased the reliability of psychiatric diagnosis. On the other hand, the limits of this approach for clinicians and researchers are becoming increasingly apparent. In particular, the assessment of subjective experience is nearly excluded on the theoretical level and undervalued on the pragmatic level, with detrimental consequences for the validity of psychiatric diagnosis, empirical research and therapeutic purposes. To correct this unfavourable development, three major approaches to the assessment of mental illness should be equally taken into account: (1) the positivistic, objectifying or 3rd-person approach as endorsed by DSM-IV and ICD-10, focusing mainly on observable behavioural symptoms; (2) the phenomenological, subject-oriented or 1st-person approach, focusing on the patient’s self-experience and exploring its basic structures, and (3) the hermeneutic, intersubjective or 2nd-person approach, mainly aiming at the co-construction of narratives and interpretations regarding the patient’s self-concept, relationships and conflicts. These three approaches will be compared regarding their respective values for psychopathological description, diagnosis, research and therapeutic purposes.
Gesehen am 17.07.2023